Optical Imaging of Neocortical Dynamics - Weber, Bruno; Helmchen, Fritjof; SpringerLink (Online service) (Totowa, NJ : Humana Press : Imprint: Humana, 2014)
The application of optical methods for investigating neocortical circuit dynamics has greatly expanded in recent years, providing novel insights into the fascinating world of brain function. Optical Imaging of Neocortical Dynamics presents a guide to these indispensible tools, which cover a broad range of spatiotemporal scales and a  large variety of signaling aspects, ranging from voltage changes to metabolic states. This detailed volume specifically explores methods that are applied in experiments on living brains (in vivo) and that relate to functional properties on the spatial scale of cortical circuits.  Beginning with an introductory section that focuses on physical fundamentals of optical imaging as well as molecular tools used for in vivo optical imaging and optogenetic control, the book continues with the most relevant methods and their applications to investigate changes in neuronal and glial activity states as well as optical imaging methods probing metabolic states.  Written for the Neuromethods series, this volume contains the kind of detail and key implementation advice that ensures successful results in the lab.   Practical and easy to use, Optical Imaging of Neocortical Dynamics serves as an ideal guide for researchers who aim to apply these highly valuable tools to their own neuroscientific studies.
Neocortex in the Spotlight: Concepts, Questions, and Methods -- Principles and Fundamentals of Optical Imaging -- Optical Properties of Neural Tissue -- Fluorescent Indicators for Functional Optical Imaging -- Optogenetic Tools for Control of Neural Activity -- In Vivo Dendritic Mapping of Sensory Inputs in Cortical Neurons -- In Vivo Population Imaging of Dendritic Integration in Neocortex -- Voltage-Sensitive Dye Imaging of Cortical Dynamics -- Two-Photon Imaging of Neuronal Network Dynamics in Neocortex -- Chronic Two-Photon Imaging of Neural Activity in the Anesthetized and Awake Behaving Rodent -- Neocortical Circuit Interrogation with Optogenetics -- Imaging of Astrocytic Activity in Living Rodents -- Imaging Morphology and Function of Cortical Microglia -- Functional Imaging of Cerebral Oxygenation with Intrinsic Optical Contrast and Phosphorescent Probes -- Laser Speckle Imaging of Cerebral Blood Flow -- Two-Photon Microscopy to Measure Blood Flow and Concurrent Brain Cell Activity.
Keywords: Neurosciences; Neurology .; Neurosciences; Neurology